Strategi Pembelajaran Di Era New Normal - Megawati M.M (Al-Ulum: Jurnal Pendidikan Islam, 2020)
This study aims to look at the learning strategies carried out during the current pandemic, where all elements are required to comply with health protocols, so that the education world today has to do something new, namely online schools or what is often called online. There are many problems in learning in the new normal when, by using internet facilities, teachers and students are required to know technology. Not only knowing technology, but teachers and students are also required to be active in the development of distance learning. Various problems arise, when learning uses an online or networked system, many students feel bored, not to mention that the internet network is not very supportive, so that learning often experiences congestion or intermittent. This type of research is a simple qualitative research, where the researcher will observe or observe research objects, then narrate them in writing. So that the results obtained, that learning learning strategies in the current New Normal era, many are using social media, such as google classroom, Whattap, zoom, and Elerning. This is done to prevent the spread of the Covid 19 virus in Indonesia. Keywords: Learning Strategy, New Normal.